Problematika dan Inovasi Pembelajaran Pada Masa Pandemi Di TK Assalam - Sovia Oktaviana (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2022)
COVID-19 is apandemic that has spread to almost all parts of the world, including Indonesia. With this pandemic, the pattern of education has changed so that the learning system has also changed from using an offline system to being online. This research is aimed at knowing the problems and innovations that can be done in learning during the COVID-19 pandemic. In collecting data, the author uses observation techniques carried out in Assalam Kindergarten. The method used in the preparation of this journal article, the researcher uses a descriptive method with qualitative research. From the results of the research, it is stated that educators use the home visit method as a countermeasure for students whose parents are constrained regarding the application of the internet and multimedia tools, Conduct group learning activities that are adapted to the child's area as an effort to optimize learning, open access to communication between educators and parents as overcoming the inability of parents to play a role as educators and learning activities are not focused on RPPH in an effort to overcome the limitations of facilities and infrastructure in students' homes